2013 IEEE International Conference on Smart Grid Communications (SmartGridComm) 2013
DOI: 10.1109/smartgridcomm.2013.6687994
|View full text |Cite
|
Sign up to set email alerts
|

Privacy-friendly appliance load scheduling in smart grids

Abstract: Abstract-The massive integration of renewable energy sources into the power grid ecosystem with the aim of reducing carbon emissions must cope with their intrinsically intermittent and unpredictable nature. Therefore, the grid must improve its capability of controlling the energy demand by adapting the power consumption curve to match the trend of green energy generation. This could be done by scheduling the activities of deferrable electrical appliances. However, communicating the users' needs about the usage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Rottondi and Verticale [7] have proposed the use of Multi-Party Computation (MPC) to facilitate privacy-friendly appliance load-scheduling. Although it addresses a similar problem, their architecture is designed for collaborative scheduling rather than incentivebased DR.…”
Section: B Privacy In Demand Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Rottondi and Verticale [7] have proposed the use of Multi-Party Computation (MPC) to facilitate privacy-friendly appliance load-scheduling. Although it addresses a similar problem, their architecture is designed for collaborative scheduling rather than incentivebased DR.…”
Section: B Privacy In Demand Responsementioning
confidence: 99%
“…However, it has been shown that these bids can be used to infer private information about consumers [2][6] [7]. The magnitude and timing of a particular bid could reveal the use of a particular type of system (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [8] proposed a secure information aggregation scheme for the smart grid. Rottondi et al [9] proposed a privacy-preserving load scheduling scheme to prevent the NILM attack. However, these schemes [7]- [9] require the use of homomorphic encryption (HE) [10]- [12] such as Paillier's cryptosystem [12], which is computationally expensive and far from practical.…”
Section: Related Workmentioning
confidence: 99%
“…Rottondi et al [9] proposed a privacy-preserving load scheduling scheme to prevent the NILM attack. However, these schemes [7]- [9] require the use of homomorphic encryption (HE) [10]- [12] such as Paillier's cryptosystem [12], which is computationally expensive and far from practical. Yan et al [13] proposed a symmetric encryption (SE) based secure communication scheme for AMI to protect from eavesdropping.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation